“Colorless-to-black” electrochromic and AIE-active polyamides: An effective strategy for the highest-contrast electrofluorochromism - Sun, Ningwei; Su, Kaixin; Zhou, Ziwei; Wang, Daming; Fery, Andreas; Lissel, Franziska; Zhao, Xiaogang; Chen, Chunhai (Macromolecules, 2020)
Electrofluorochromic (EFC) materials have gained extensive attention owing to their interesting modulations of fluorescence by an electric stimulus. However, the limited performances, especially the low fluorescence on/off contrast, significantly hampered their further applications. Herein, we design a new strategy to achieve high-contrast electrofluorochromism by combinations of “colorless-to-black” electrochromism and highly fluorescent AIE activity. Given the effective fluorescence quenching effect and high solid-state fluorescence, a fluorescence contrast of 838 is realized, to the best of our knowledge, the highest reported so far. Furthermore, to explore the structure-property relationships, we also separated the E/Z isomers of tetraphenylethylene (TPE) and studied the properties of the three electroactive/fluorescent polymers (11TPE-PA, E-12TPE-PA, and Z-12TPE-PA) derived from different TPE derivatives and isomers. The three branches of polymers all exhibited AIE-active and “colorless-to-black” electrochromic (EC) properties. In addition to the ultrahigh fluorescence contrast, Z-12TPE-PA also integrated high electrochromic contrast (Δ% T = 92%), short response time (0.6 s/0.3 s), and excellent switching stability (300 cycles), paving the way for the applications in various electronic applications. The study will provide novel insights into the future design and development of high-performance EC/EFC materials.
CRIS-Team Scopus Importer:2022-04-14